Geochemical and Thermodinamic Modeling of Segara Anak Lake and the 2009 Eruption of Rinjani Volcano, Lombok, Indonesia - Solikhin, Akhmad; Kunrat, S. I.; Bernard, A.; Barbier, B.; Campion, R. (Geological Agency, 2010)
DOI: 10.17014/ijog.v5i4.106Rinjani is the second highest volcano in Indonesia with an elevation of 3726 m above sea level. The steep and highest cone of Rinjani consists mainly of loose pyroclastic ejecta and contains a crater with a few solfataras. The West of this cone is Segara Anak caldera. The western side of the caldera is occupied by a 230 m deep lake, covering an area of 11 km² and its volume was (before the 2009 eruption) estimated 1.02 km3. This is probably the largest hot volcanic lake in the world.The lake water is neutral (pH: 7-8) and its chemistry dominated by chlorides and sulfates with a relatively high TDS (Total Dissolved Solids: 2640 mg/l). This unusual TDS as well as the lake surface temperatures (20 - 22°C) well above ambient temperatures (14 - 15°C) for this altitude, reflect a strong input of hydrothermal fluids. Numerous hot springs are located along the shore at the foot of Barujari volcanic cone. Bathymetric profiles show also several areas with columns of gas bubbles escaping from the lake floor indicating a significant discharge of CO gas into the lake. The mass and energy balance model of Rinjani Crater Lake produce total heat lost value on the average of 1700 MW. Most of the heating periods of the lake occurred when the heat released by the surface of the lake to the atmosphere was lower than the heat supplied from the hydrothermal system. Peaks of heat losses correspond to period of strong winds. Crater lake monitoring can provide a basic information about deep magmatic activity and surface processes that occur in the volcano. The monitoring also contributes to predict the next eruption in order to improve mitigation of volcanic eruption. Precursory signals of the May 2009 eruption can be seen from significant changes in the temperature and chemistry of some of the hot springs, the increase of Fe concentrations in spring #54, chemical plume of low pH and dissolved oxygen, acidification of Segara Anak Lake, and increasing of lake surface temperatures. The new lava flow from May - August 2009 eruption covers an area of 650,000 m2. The shoreline was significantly modified by the entry of lava into Segara Anak Lake. The area of the lake is reduced by 460,000 m2.